God’s λόγος in James and Early Judaism - Allen, Joseph G. (Novum Testamentum, 2025)
The referent of the λόγος in James 1 is the subject of ongoing debate. One aspect of the debate that has not been adequately discussed is why James makes use of λόγος language in particular, as opposed to any of the other soteriological terms available to the author. This study argues that James does so because it is alluding to the powerful, creative, and instructive λόγος known from the Septuagint. Further, it will be seen that James’s appropriation of these texts is analogous to the way these texts were received by early Jewish writers like Aristobulus, Pseudo-Solomon, and Philo. This study concludes by revisiting the question of James’s relationship to other early Christian soteriologies.